Analisis Usaha dan Strategi Pemasaran Agroindustri Tahu (Studi Kasus: Tahu Bapak Kuswardi di Jl. Gajah Tunggal Desa Tualang Kabupaten Siak) - Putri, Isnaini; Yusmini, Yusmini; Edwina, Susy (Universitas Galuh, 2025)
Mr. Kuswardi's tofu agroindustry has been operating since 1996. Despite its longevity, the business faces several challenges, including declining demand due to market competition and limited promotional efforts, which still rely on word of mouth. Additionally, the utilization of tofu waste remains suboptimal, even though tofu dregs have economic potential if processed properly. This study aims to analyze the business performance and formulate appropriate marketing strategies for the tofu agroindustry. The research was conducted from January to April 2025 using a case study method. Respondents consisted of those involved in determining SWOT and AHP components. The results showed that the total cost of raw materials was IDR 22.137.500,00, and the total production cost in December 2024 was IDR 40.748.438,00. The business earned total revenue of IDR 57,750,000.00 and a profit of IDR 17.001.563,00. The final product value was IDR 30.000,00, and the value of other inputs was IDR 1.720,00. The Revenue-Cost Ratio (RCR) of 1.4 indicates that the business is financially feasible. The added value per unit of tofu production was IDR 16.780, with a value-added ratio of 56%. Marketing is carried out through a single channel: zero-level marketing, where products are sold directly to consumers. The recommended marketing strategy for Mr. Kuswardi's tofu agro-industry is to collaborate with local shops or stalls so that product distribution is more stable and even and to utilize social media as a means of promotion to expand market reach.